Editorial - Barboza Jiménez, Lucrecia (2012)
With pleasure, we present a new issue of the Library. Includes research interests on the following topics: archetypes librarians, information literacy and cloud computing. In the article on the archetypes, the author states that the library profession, as with other disciplines, is exposed to a series of stereotypes. Such impressions and beliefs cause people, motivated by prejudice, no inroads into a fascinating discipline as a result, affect the enrollment of freshmen. This paper presents the status of the School of Library, Documentation and Information, National University, and poses a methodological approach in order to improve the design of the library between secondary student population.